2018
DOI: 10.22334/jihm.v6i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Layanan Akademik Dan Harga (Biaya Pendidikan) Terhadap Word of Mouth Melalui Kepuasan Mahasiswa Sebagai Variabel Intervening (Studi Pada LPK Sekolah Perhotelan Bali)

Abstract: In Indonesia, particularly in Bali, these are a lot of Training Centers (LPK) in tourism sectors which grow and evolve rapidly, by selling trend working on Cruise ship and over seas such as in hotels and restaurants, it is the main attraction for prospective students to continue their education after they have completed their educations in vocational or high school. The purposes of this study are to describe the effect of the quality of academic services to the student’s satisfaction, the effect of price (educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The findings from this study conclude that the cost of education has a positive and significant influence on student satisfaction. This is in line with the results of research conducted by Wijaya, et al (2016) revealed that the price or cost of education has a positive and significant effect on student satisfaction. Likewise with the results of Gofur's research (2019), Fachmy, et al (2019), and Sari & Kurnia (2018 confirm that price has a positive and significant effect on satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…The findings from this study conclude that the cost of education has a positive and significant influence on student satisfaction. This is in line with the results of research conducted by Wijaya, et al (2016) revealed that the price or cost of education has a positive and significant effect on student satisfaction. Likewise with the results of Gofur's research (2019), Fachmy, et al (2019), and Sari & Kurnia (2018 confirm that price has a positive and significant effect on satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…The cost of education is inseparable from 2, 4., March 2023 student satisfaction. This is because competitive education costs emphasize student satisfaction (Kinung & Rudini, 2020;Wijaya et al, 2016).…”
Section: Figure 4 T Value Analysis Of Fit Model With Thick Linesmentioning
confidence: 99%
“…In addition to educational facilities in the form of facilities and infrastructure, attention to competitive education costs emphasizes student satisfaction in order to attract prospective students, and serve and retain them (Wijaya et al, 2016). In the end, the factor of education costs that must be incurred by students also needs to be considered because the cost of education can also affect student satisfaction (Kinung & Rudini, 2020).…”
Section: Introductionmentioning
confidence: 99%